Effect of interleukin-4 on vascular endothelial growth factor production in rheumatoid synovial fibroblasts - Hong, K-H (Blackwell Science Inc, 2007)
Interleukin (IL)-4 has been demonstrated to have anti-inflammatory and anti-tumour activity. Because aberrant angiogenesis is a significant pathogenic component of tumour growth and chronic inflammation, we investigated the effect of IL-4 on the production of vascular endothelial growth factor (VEGF) by synovial fibroblasts derived from patients with rheumatoid arthritis (RA). Fibroblast-like synoviocytes (FLS) were prepared from synovial tissues of RA and incubated with different concentrations of IL-4 in the presence or absence of transforming growth factor (TGF)-β. VEGF level was measured by enzyme-linked immunosorbent assay and semiquantitative reverse transcription–polymerase chain reaction. Treatment of FLS with IL-4 alone caused a dose-dependent increase in VEGF levels. In contrast, IL-4 exhibited the inhibitory effect on VEGF production when FLS were stimulated with TGF-β. Combined treatment of IL-4 and IL-10 inhibited TGF-β-induced VEGF production in an additive fashion. TGF-β increased the induction of cyclooxygenase-2 mRNA, which was inhibited significantly by the treatment of IL-4. NS-398, a COX-2 inhibitor, inhibited TGF-β-induced VEGF production in a dose-dependent manner. Furthermore, exogenous addition of prostaglandin E(2) (PGE(2)) restored IL-4 inhibition on TGF-β induced VEGF production. Collectively, our results suggest that IL-4 have an anti-angiogenic effect, especially in the inflammatory milieu of RA by inhibiting the VEGF production in synovial fibroblasts.